Access to Mass Media and Rejection of Gender Inequitable Norms among Unmarried Youth in Dar es Salaam, Tanzania (Tanzania Journal for Population studies and Development, 2012)
Despite extensive evidence on the link between gender norms and adolescent sexual and reproductive health (ASRH), less research has been conducted to assess the role that access to mass media plays in shaping these norms. This article is based on a study that sought to contribute to filling this research gap. The primary objective of the study was to determine young males’ and female’s attitudes and perceptions towards traditional gender norms. The second objective was to investigate the association between mass media consumption by youth and rejection or acceptance of gender equitable norms. Using a scale called Gender Equitable Men (GEM), this study conducted a cross-sectional survey among 777 unmarried youth (52.1% male and 47.9% female) in selected wards of Temeke municipality in Dar es Salaam, Tanzania between December 2011 and January 2012. The results show that youth support to gender equitable norms is relatively high (91% male and 83% female). Also, there are important correlations between youth’ support for gender-equitable norms and their background characteristics. Comparatively, unmarried male youth have higher support to gender equitable norms than unmarried female youth. However, the relationship between access to mass media and support for gender equitable norms is not linear. The conclusion is that access to mass media alone is not sufficient to determine support to gender equitable norms, which later impact on adolescent sexual and reproductive health. Thus, more attention needed on broad social contexts that mediate linkage between the two. Programmatic and policy implications of these findings are also discussed.